0.04(y-8)+0.02y=0.16y-0.9

Simple and best practice solution for 0.04(y-8)+0.02y=0.16y-0.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.04(y-8)+0.02y=0.16y-0.9 equation:


Simplifying
0.04(y + -8) + 0.02y = 0.16y + -0.9

Reorder the terms:
0.04(-8 + y) + 0.02y = 0.16y + -0.9
(-8 * 0.04 + y * 0.04) + 0.02y = 0.16y + -0.9
(-0.32 + 0.04y) + 0.02y = 0.16y + -0.9

Combine like terms: 0.04y + 0.02y = 0.06y
-0.32 + 0.06y = 0.16y + -0.9

Reorder the terms:
-0.32 + 0.06y = -0.9 + 0.16y

Solving
-0.32 + 0.06y = -0.9 + 0.16y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.16y' to each side of the equation.
-0.32 + 0.06y + -0.16y = -0.9 + 0.16y + -0.16y

Combine like terms: 0.06y + -0.16y = -0.1y
-0.32 + -0.1y = -0.9 + 0.16y + -0.16y

Combine like terms: 0.16y + -0.16y = 0.00
-0.32 + -0.1y = -0.9 + 0.00
-0.32 + -0.1y = -0.9

Add '0.32' to each side of the equation.
-0.32 + 0.32 + -0.1y = -0.9 + 0.32

Combine like terms: -0.32 + 0.32 = 0.00
0.00 + -0.1y = -0.9 + 0.32
-0.1y = -0.9 + 0.32

Combine like terms: -0.9 + 0.32 = -0.58
-0.1y = -0.58

Divide each side by '-0.1'.
y = 5.8

Simplifying
y = 5.8

See similar equations:

| -14=(6/7x)-4-7x | | 10x=3+12 | | (3w^2-7w+2)+(-4w^2+5w+1)= | | 5x-(7)=7x-(17) | | -3x-6=18forx | | 10x+4x+3+7=9x+3+4x | | 18=3d | | 8=(10)w(2) | | ln(y)=2ln(x)+ln(10) | | 23x+21x=72 | | h-23=27 | | 9i*12i= | | 2(x+1)+5=-4(x-2) | | 5(3x+7)=-19+39 | | 17+p=30 | | 4+5lnx=19 | | 5u^3+4u^2-25u-20=0 | | 5(5x+2)-5= | | 4(-6x-2)+10=8(-3x-1)+14 | | n/-20=0 | | -4(15y+1)+8=20(-3y+5)-102 | | -344=8(8v-3) | | (X^3-7)/(x-2) | | 18x=288 | | 1(-4x-5)+7=4(-1x-4)+18 | | x+5=8+x | | s^2=323 | | 3+3x=3x+2 | | 3/4(2?3M)=24 | | 26/y=2 | | -147=3k-3(8k+7) | | -1(x+3)-3=-6(x+8) |

Equations solver categories